2006
DOI: 10.1021/bc060044i
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Quantum Dot−Peptide Bioconjugates for Selective Intracellular Delivery

Abstract: We demonstrate the use of self-assembled luminescent semiconductor quantum dot (QD) -peptide bioconjugates for the selective intracellular labeling of several eukaryotic cell lines. A bifunctional oligoarginine cell penetrating peptide (based on the HIV-1 Tat protein motif) bearing a terminal polyhistidine tract was synthesized and used to facilitate the transmembrane delivery of the QD bioconjugates. The polyhistidine sequence allows the peptide to self-assemble onto the QD surface via metal-affinity interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
290
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(317 citation statements)
references
References 57 publications
25
290
2
Order By: Relevance
“…This modification also allowed active targeting of the nucleus in spite of the increased size of the particles (14.1-18 nm in diameter) [36]. We should mention that the cellular uptake can be influenced not only by the conjugation of CPPs, but also by the number of QD-associated CPPs and the cell-type, which has been confirmed by Delehanty et al [88] The functionalization of QDs with CPPs can facilitate their transport across the plasma membrane, and thus enable these particles to cross the blood-brain barrier (BBB). Tat-modified QDs, for example, were successfully used by Santra et al to fluorescently label brain tissue of rodents (SD adult rats, Sprague-Dawley rats) [89].…”
Section: Delivery Of Nanoparticles Using Cpps Quantum Dotssupporting
confidence: 54%
“…This modification also allowed active targeting of the nucleus in spite of the increased size of the particles (14.1-18 nm in diameter) [36]. We should mention that the cellular uptake can be influenced not only by the conjugation of CPPs, but also by the number of QD-associated CPPs and the cell-type, which has been confirmed by Delehanty et al [88] The functionalization of QDs with CPPs can facilitate their transport across the plasma membrane, and thus enable these particles to cross the blood-brain barrier (BBB). Tat-modified QDs, for example, were successfully used by Santra et al to fluorescently label brain tissue of rodents (SD adult rats, Sprague-Dawley rats) [89].…”
Section: Delivery Of Nanoparticles Using Cpps Quantum Dotssupporting
confidence: 54%
“…69 Bioconjugation of QDs with cell-penetrating polyargininetype peptide has resulted in partial colocalization of the QDs within endosomes. 70 Furthermore, coating with hyperbranched copolymer ligands has demonstrated an endosomedisrupting effect (endosomolysis). 71 The osmotic-imbalance strategy can also be employed by dipeptides that are cleaved by lysosomal dipeptidase.…”
mentioning
confidence: 99%
“…QDs capped with compact carboxylated ligands have shown reasonable rates of nonspecifi c endocytosis (Jaiswal et al 2003), however receptor-mediated uptake has demonstrated better effi ciency by specifi cally targeting receptors displayed on the cell surface (Chan and Nie 1998;Lidke et al 2004;Bharali et al 2005). As expected, ligands previously identifi ed to cue and facilitate receptormediated endocytosis continue to function effectively when attached to QD surfaces resulting in effi cient delivery of the modifi ed nanoparticle assembly within cells, but with the potential drawback of the cargoes remaining largely confi ned inside the endosomes (Delehanty et al 2006). If the intended destination of a QD bioconjugate is a specifi c organelle or general release into the cytosol, this perpetual confi nement presents a signifi cant obstacle.…”
Section: Cell Labelingmentioning
confidence: 89%
“…The authors found negligible toxicity in these model cells and attribute this result to appropriate sequestration of the core-shell material and the biocompatibility of the surface-bound PEG. Mattoussi's group has reported on the dosage effects of QDs on different cell lines (Delehanty et al 2006). They found that acute (1 hour) versus chronic (continuous) exposure and labeling of different concentrations of QDs to two cell lines resulted in a signifi cantly different impact on subsequent cellular viability.…”
Section: Toxicitymentioning
confidence: 99%